SISTEM PENDIDIKAN ISLAM PADA MASA KHULAFAUR RASYIDIN: SEBUAH TINJAUAN HISTORIS - Azidnia Fauza; Alfauzan Amin; Saepudin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Religious education for Muslims is an Islamic education derived from the Qur'an and the Sunnah. This article examines the dynamics of the transformation and progress of Islamic education after the death of the Prophet Muhammad, specifically the changes in Islamic education during the era of the Rightly Guided Caliphs. It explains how the educational system was implemented in each caliphate and the different situations, as well as the factors underlying the educational systems implemented at that time. The findings of this study indicate that the educational pattern during the era of Caliph Abu Bakr remained generally similar to that of the Prophet Muhammad. The development of Islam progressed rapidly during the era of Caliph Umar ibn al-Khattab, which was succeeded by Caliph Uthman ibn Affan. However, several fundamental changes occurred, particularly in the policies and educational methods used.